Effects of Different Elicitors on Micropropagation, Biomass and Secondary Metabolite Production of Stevia rebaudiana Bertoni—A Review - Kamelia Miladinova-Georgieva; Maria Geneva; Ira Stancheva; Maria Petrova; Mariana Sichanova; Elisaveta Kirova (Plants, 2022)
Stevia rebaudiana Bertoni is a valuable plant whose products are increasingly used in medicine, pharmacy and the food industry. This necessitates the use of biotechnological approaches for its mass propagation. Establishing optimal conditions for in vitro cultivation is essential for obtaining high biomass and secondary metabolites production. A large number of articles considering the role of plant growth regulators and other additives in the culture medium in the growth and development of Stevia are available in the literature. However, there are no summarized data about the use of nanoparticles in Stevia tissue cultures. Therefore, this review also includes the research conducted so far on the effect of nanoparticles on Stevia micropropagation. Furthermore, the influence of different elicitors on secondary metabolite production and antioxidant activity of in vitro-cultivated Stevia plants have been discussed. By referring to the collected literature, we concluded that biotechnological approaches applied to S. rebaudiana cultivation might improve the agronomic traits of plants and steviol glycosides production.